1996
DOI: 10.1177/039139889601900708
|View full text |Cite
|
Sign up to set email alerts
|

Left Intraventricular Balloon Pump Optimization during Intractable Cardiac Arrest

Abstract: This work aims to determine optimal balloon shape and volume during left intraventricular balloon pumping (IABP) in the fibrillating dog heart. A balloon volume equal to the left ventricular end-diastolic volume (LVEDV) maintained a higher systolic aortic pressure and flow (106.4 +/- 2.7 mmHg and 84.7 +/- 2.35 ml/kg/min, x +/- SEM, respectively) than a 25% smaller (97.8 +/- 3.3 mmHg, P = 0.002 and 63.7 +/- 4.1 ml/kg/min, P = 0.002, respectively) or a 25% larger balloon (87.4 +/- 2.3 mmHg, P = 0.002 and 70.9 +/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Previous IVBP studies have tested flexible balloons for LV implantation in animal models with different volumes (from 40 to 110 mL) and geometries, such as: spherical, tomato, pear, and an LV cast at end-diastole. 6,8,10,12,13 Interestingly, only 1 study has customized the balloon volume to the LV shape: Stamatelopoulos et al evaluated 3 balloon volumes (LVEDV and LVEDV ± 25%) on IVBP function. 13 Results indicated that an intraventricular balloon volume equal to the corresponding LVEDV generated the largest MAP and AoF.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous IVBP studies have tested flexible balloons for LV implantation in animal models with different volumes (from 40 to 110 mL) and geometries, such as: spherical, tomato, pear, and an LV cast at end-diastole. 6,8,10,12,13 Interestingly, only 1 study has customized the balloon volume to the LV shape: Stamatelopoulos et al evaluated 3 balloon volumes (LVEDV and LVEDV ± 25%) on IVBP function. 13 Results indicated that an intraventricular balloon volume equal to the corresponding LVEDV generated the largest MAP and AoF.…”
Section: Discussionmentioning
confidence: 99%
“…6,8,10,12,13 Interestingly, only 1 study has customized the balloon volume to the LV shape: Stamatelopoulos et al evaluated 3 balloon volumes (LVEDV and LVEDV ± 25%) on IVBP function. 13 Results indicated that an intraventricular balloon volume equal to the corresponding LVEDV generated the largest MAP and AoF. To the best of our knowledge, there are no IVBP studies that aimed to prevent mitral regurgitation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations